Ayurveda and lifestyle modification: research to practice - Chattopadhyay, Kaushik (2017)
The global burden of non-communicable diseases is rapidly increasing, and the essential management strategy is to follow a healthy lifestyle. Ayurveda can play a major role in this aspect, as the primary aim of Ayurveda is to prevent diseases by following a healthy lifestyle. However, in order to implement such classical knowledge (that is, healthy lifestyle based on Ayurvedic principles) into real practice, a systematic process needs to be followed. This systematic process must include robust research studies (that is, development and evaluation of Ayurveda-based lifestyle intervention) and behaviour change of people. This paper describes these two important steps in detail. In conclusion, there is a huge scope of implementing classical Ayurvedic knowledge into real practice, which will be beneficial to all of society.